Religious-Nationalism Based Character Education ‎in Traditional Pesantren - Rahman, Yulia (TADRIS: Jurnal Pendidikan Islam, 2022)
This research was motivated by the rise of accusations of radicalization through Islamic educational institutions, especially traditional pesantren. The learning process in traditional pesantren that seem unable to train students' critical thinking skills is considered a factor in the ease with which radicalism grows in these institutions. This study aims to determine how the implementation of religious-nationalism-based character education in traditional pesantren. The focus of the research is on nationalism-religious character education in learning materials and pesantren culture. This type of research is a mix-method research with field research techniques. The data were collected by means of documentation, interviews and questionnaires. The questionnaire is quantitative data which is analyzed with a qualitative paradigm. These data are sourced from three traditional Islamic boarding schools in Padang. The results of this study conclude that nationalism-religious-based character education in traditional Pesantren is applied in moral learning materials that refer to the kitab kuning and Islamic religious subject textbooks. In addition, nationalist-religious character education is also developed through a pesantren culture which is thick with the values ​​of love for the homeland, unity, tolerance, and democracy. This conclusion is supported by the nationalist-religious attitude of the majority of santri in traditional pesantren. The results of this study strengthen the conclusions of previous studies which stated that Islamic boarding schools teach an accommodative, pluralist attitude and reject radicalism.